Value Relevance of Accounting Information: A Systematic Bibliographic Review of Global Trends and Emerging Research - Joni Devitra; Chintiya Mayliana Diaz Putri (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The value relevance of accounting information remains a central concern in accounting research. The globalization of reporting standards (International Financial Reporting Standards [IFRS]) and the rise of non-financial disclosures (environmental, social, and governance [ESG] factors and corporate governance) have introduced both opportunities and complexities in how financial information influences investors’ economic decisions, particularly in emerging markets. Objective: This study examines the evolution, thematic trends, key variables, and research directions in the value relevance literature based on international publications indexed in Scopus from 2014 to 2024. Methods: A PRISMA-compliant systematic bibliographic review was conducted. Data were sourced from Scopus using the keywords “value relevance” and “earnings relevance,” restricted to English-language, open-access publications in the subject areas of Business, Management, Accounting, Economics, and Finance published between 2014 and 2024. Results: Publication volume grew substantially between 2014 and 2024, with a brief decline in 2020 attributable to pandemic-related disruptions, followed by recovery from 2021 onward. Developed countries—particularly the United Kingdom, Australia, Italy, and the United States—dominate the literature. The dominant variables remain earnings, book value, and IFRS adoption, although a discernible shift toward non-financial factors (ESG, corporate social responsibility [CSR], and corporate governance) is evident. Institutional context, earnings quality, governance mechanisms, and reporting standard consistency emerged as key determinants of value relevance strength. Conclusion: The value relevance of accounting information is a growing and evolving field of research. While foundational variables retain their centrality, the integration of non-financial disclosures and institutional context represents the frontier of the field. This study contributes a structured synthesis of a decade of global evidence, identifying underexplored themes that warrant future investigation.